Clinical Profile and Outcome of Acute Poisoning Cases in Children Living in a Rapidly Urbanizing Area - Islam, Md Nurul; Ringku, Naimur Rahman; Islam, Md Saiful (Medicine Today, 2021)
Introduction: Acute poisoning is a common childhood emergency in Bangladesh. In many cases history and clinical features fail to identify the offending agent. This study was done to identify the specific clinical findings related with the source of poisoning and assess the outcome. Materials and Methods: It was a prospective study done from January to June 2020, among 75 indoor children of Tangail District Hospital. A preformed structured questionnaire was filled up by data collected from direct interview with the parents or caregivers, hospital records, during clinical examination. Results: We found the mean age of the study population 5.5±1.5 years having male preponderance 1.6:1 in ratio. Kerosene 16(21.33%) and organophosphorus compound 15(20%) were the most common etiological agents and accidental (85%) was the most common mode of poisoning. Most of the cases were asymptomatic 25(33.3%). We encountered only 5(6.6%) death having 62(82.6%) complete recovery. Conclusion: Acute poisoning still remains a major cause of child death in Bangladesh. History remains the main information for early diagnosis. We should take necessary steps to prevent exposure to poisonous material in children to reduce related burden of hospitalization, mortality and morbidity. Medicine Today 2021 Vol.33(2): 156-159